Diabetes Risk Factor Screening in the Adult Population Using the Findrisc Score and Oral Glucose Tolerance Test - Fazidah Aguslina Siregar; Tri Makmur; Asfriyati Asfriyati (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
The global rise in the prevalence of type 2 diabetes is heavily concentrated in urban centers, yet more than half of those affected remain completely undiagnosed. Non-invasive clinical risk assessment tools can indeed stratify population risk, but there remains a gap in operational validation regarding the Finnish Diabetes Risk Score (FINDRISC) when combined with biochemical verification in urban populations in Indonesia. This study evaluated the diagnostic accuracy of the FINDRISC questionnaire in identifying undiagnosed type 2 diabetes and dysglycemia, using the oral glucose tolerance test (OGTT) as the gold standard. The study was conducted in the community using a cross-sectional design with non-random, purposive sampling in six subdistricts to recruit 300 adults aged 30–75 years. The 8-item FINDRISC questionnaire and anthropometric measurements were administered, followed by biochemical verification via OGTT and chi-square analysis. FINDRISC categorized 33.7% of participants as low-risk and 5.3% as high-risk, while the OGTT confirmed 18.0% had prediabetes and 30.0% had diabetes. Increased risk was significantly correlated with advanced age, high body mass index (BMI), central obesity, lack of physical activity, inadequate fruit and vegetable intake, treatment for hypertension, a history of hyperglycemia, and family predisposition (p<0.005). Among low-risk respondents, 68.3% had normal glucose levels, whereas 61.8% of high-risk individuals had glucose levels indicative of diabetes (p<0.005). The integration of the non-invasive FINDRISC triage tool prior to laboratory testing offers a resource-efficient sequential screening framework for urban primary health care. This strategy optimizes the allocation of institutional resources, detects subclinical dysglycemia early, and enables targeted preventive lifestyle interventions.Keywords: Type 2 Diabetes, FINDRISC, Oral Glucose Tolerance Test, Mass Screening, Public Health Surveillance.